PENGARUH TAX AVOIDANCE TERHADAP UTANG PT GARUDA INDONESIA PERIODE 2014 – 2019 YAN G TERDAFTAR DI BEI - Richard Jonathan Ginting; Paul Eduard Sudjiman (Jurnal Ekonomis, 2021)
This study discusses how the influence of tax avoidance or what is usually referred to as tax avoidance on debt that occurs in pt manufacturing companies. Garuda Indonesia Airways is listed on the Indonesia Stock Exchange. This research is a quantitative research with data obtained secondaryly. With data obtained from the annual report of PT. Garuda Indonesia Airways from 2014 to 2019. The data used in this study uses Pph Agency, profit before tax, tax avoidance and debt. Which pph agency and profit before tax is used as a factor in determining tax avoidance. The authors conducted data processing using analysis tools in the form of SPSS version 24 using descriptive analysis, simple linear regression test, validity test, T test and R- Square Test. The results of this study show that in this study tax avoidance does not have a significant influence on the amount of debt owned by PT. Garuda Indonesia Airways.